2014/2015 survey on University of Maribor as a sustainable and socially responsible university. (2015) - Mulej, Matjaž; Čagran, Branka
Sustainability and social responsibility are, officially and practically, preconditions for the humankind to survive. Few people are aware of this fact. Awareness enables action. Insight into awareness enables impact over awareness. The University of Maribor (UM), Slovenia is trying to make its contribution, which is discussed here in terms of a survey as a first step in transforming the political statements into a practiced reality. University of Maribor (UM) passed documents in 2012-2014 that call UM the sustainable and socially responsible University (SSRUM). They include an official action plan for the period 2014-2020. Perhaps UM's students and employees know enough about SSRUM and can/will or can/will not join the needed actions. The survey presented here might help and be usable elsewhere, too. There are three similar survey questionnaires; we present here the one for students and the specifics for employees.